MEASUREMENT OF OVARIAN FOLLICLES AND VAGINAL TEMPERATURE OF BALI CATTLE THAT EXPERIENCE SILENT HEAT - Pemayun, Tjok Gde Oka; Kendran, Anak Agung Sagung; Gunawan, I Wayan Nico Fajar (Buletin Veteriner Udayana, 2021)
This study aimed to improve Bali cattle's efficiency and productivity by measuring ovarian follicles and vaginal temperature in Bali cattle that experienced a silent heat using ten bali cattle with normal estrus and bali cattle that experience a silent heat. The research samples were divided into two groups: Bali cattle that showed normal estrus (grup I) and Bali cattle that experienced a silent heat (grup II), with each group consisted of 5 replications. Furthermore, all the cows were measured for vaginal measurements at the time of estrus and 24 hours after estrus. While ovarian follicles are measured at the time of estrus. The results showed that the average vaginal temperature of Bali cattle was 38.40 ± 0.130 C and 38.04 ± 0.130 C respectively for Bali estrus cattle and Bali cattle which experienced a silent heat and statistically showed a significant difference (P<0.05). The Bali cattle follicles' average diameter is 10.60 ± 1.14 and 7.32 ± 0.37 mm, respectively, for the normal estrus and which experience a silent heat, and statistically show a significant difference (P<0.05). From the results of the study, it can be concluded that the vaginal temperature of bali cattle with normal estrus is higher than that of bali cattle which experience a silent heat, and ovarian follicle diameter in normal estrus is greater than the diameter of the ovarian follicles of bali cattle that experience silent heat.